Mighty be our powers : how sisterhood, prayer, and sex changed a nation at war : a memoir - Gbowee, Leymah; Mithers, Carol Lynn. (New York : Beast ; London : Perseus Running [distributor], 2011)
In a time of death and terror, Leymah Gbowee brought Liberia's women together--and together they led a nation to peace. As a young woman, Gbowee was broken by the Liberian civil war, a brutal conflict that tore apart her life and claimed the lives of countless relatives and friends. As a young mother trapped in a nightmare of domestic abuse, she found the courage to turn her bitterness into action, propelled by her realization that it is women who suffer most during conflicts--and that the power of women working together can create an unstoppable force. In 2003, the passionate and charismatic Gbowee helped organize and then led the Liberian Mass Action for Peace, a coalition of Christian and Muslim women who sat in public protest, confronting Liberia's ruthless president and rebel warlords, and even held a sex strike. With an army of women, Gbowee helped lead her nation to peace.--From publisher description.
Prologue -- The world was mine -- "We'll soon put an end to the problem" -- I am too young to die! -- Trapped -- Helpless in a strange place -- A glimpse of peace -- "Yes, you can" -- Taking on "Taylor's boys" -- A new home with Geneva -- Helping women find their voices -- The women in peace-building network is born! -- "Don't ever stop" -- Standing up to Charles Taylor and sitting down for peace -- When peace talks are just talk, take action -- Is the war really over? -- Time to move on -- An unthinkable loss -- Building a new women's network -- Pray the devil back to hell -- Helping my country -- The story doesn't end.
Includes index.
Keywords: Gbowee, Leymah; Gbowee, Leymah; Women of Liberia Mass Action for Peace; Women of Liberia Mass Action for Peace; Women political activists -- Liberia -- Biography; Women pacifists -- Liberia -- Biography; Women -- Liberia -- Social conditions; Peace movements -- Liberia; Violence -- Liberia; Women political activists -- Liberia -- Biography; Pacifism -- Liberia -- Biography; Women -- Liberia -- Social conditions; Liberia -- History -- Civil War, 1999-2003.; Liberia -- History -- Civil War, 1989-1996.; Liberia -- History -- 1999-2003, Civil War; Liberia -- History -- 1989-1996, Civil War; Autobiographie